ANALISIS PENINGKATAN TEBAL PERKERASAN RUNWAY DI LANUD RADEN SADJAD RANAI KABUPATEN NATUNA - Budi Setiawan; Sahat Martua Sihombing; Lydia Darmiyanti (Fakultas Teknik Universitas Krisnadwipayana, 2022)
The Riau Islands Province is currently one of the provinces in Indonesia which is experiencing significantdevelopment, especially in the tourism sector. This condition affects the number of use of commercial aviationservices that will enter and leave our area both now and in the future. Raden Sadjad Ranai Lanud, Natuna Regency isthe gateway to Natuna Island and is the main airport which currently serves international standard domestic flights.The airport uses a single runway which is the simplest configuration. Analysis of the flexible pavement thickness ofthe runway at Raden Sadjad Ranai Air Force Base in Natuna Regency aims to determine the thickness of the flexiblepavement layer of the runway at the airport. The planning method used is the FAA (Federal Aviation Administration)method. The first step that needs to be considered is the CBR (California Bearing Ratio) value of the subgrade, thedetermination of the modulus of subgrade value, the selection of the plan plane, the MTOW of the aircraft, the loadof one aircraft wheel (W2), corrected departure (R2), the load of one wheel of the aircraft plan (W1 ) and theequivalent annual deparature of the planned aircraft (R1). This pavement thickness analysis uses the plan C-130Hercules and Boeing 737-500 aircraft. Based on the data obtained, then the plan aircraft MTOW value, thesubgrade classification value according to the FAA is plotted on the FAA flexible pavement thickness evaluationcurve so that the pavement thickness is obtained, the results of this study indicate that for plan aircraft C-130Hercules and Boeing 737-500 required surface coarse thickness 21.59 cm by 41.91 cm coarse subbase layer. Theresults with this comparison COMFAA application required a surface coarse pavement thickness of 20 cm with 30cm of base coarse layer and 12.24 cm of subbase layer